2017
DOI: 10.1101/219683
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Higher-order inter-chromosomal hubs shape 3-dimensional genome organization in the nucleus

Abstract: Eukaryotic genomes are packaged into a 3-dimensional structure in the nucleus of each cell.There are currently two distinct views of genome organization that are derived from different technologies. The first view, derived from genome-wide proximity ligation methods (e.g. Hi-C), suggests that genome organization is largely organized around chromosomes. The second view, derived from in situ imaging, suggests a central role for nuclear bodies. Yet, because microscopy and proximity-ligation methods measure differ… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
6
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 104 publications
2
6
0
Order By: Relevance
“…5A,B). This 310 suggests multiple active rRNA transcription sites are in close spatial proximity with adjacent 311 pericentromeric regions, as recently observed based on proximity ligation (Quinodoz et al 2017). 312 Importantly, we also identified CHARRs on multiple non-pericentromeric regions, suggesting 313 their potential interactions with chromatin in both cis-and trans-modes.…”
Section: Cis-and Trans-acting Repeat-derived Rnas On Chromatin 303supporting
confidence: 71%
See 1 more Smart Citation
“…5A,B). This 310 suggests multiple active rRNA transcription sites are in close spatial proximity with adjacent 311 pericentromeric regions, as recently observed based on proximity ligation (Quinodoz et al 2017). 312 Importantly, we also identified CHARRs on multiple non-pericentromeric regions, suggesting 313 their potential interactions with chromatin in both cis-and trans-modes.…”
Section: Cis-and Trans-acting Repeat-derived Rnas On Chromatin 303supporting
confidence: 71%
“…3A). The 256 association of rRNAs with heterochromatin agrees with a recent observation that transcriptionally 257 inert centromere-proximal regions tend to be organized around the nucleolus in 3D 258 genome (Quinodoz et al 2017). However, since rRNAs are assembled into ribosomes, rather than 259 processed into small RNAs, it is unlikely that they contribute to heterochromatin functions.…”
supporting
confidence: 78%
“…The investigation of the 3D structure of chromosomes in the nucleus of cells, and its functional implications, has been revolutionized by new technologies such as Hi‐C (Lieberman‐Aiden, van Berkum, Williams, et al, ), or the more recent GAM (Beagrie, Scialdone, Schueler, et al, ) and SPRITE (Quinodoz et al, ). Such technologies allow to measure the frequency of physical contacts between deoxyribonucleic acid (DNA) sites genome‐wide, returning for instance the network of interactions formed by regulatory regions and their target genes.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, TADs appear to form higher‐order structures (meta‐TADs) (Fraser, Ferrai, Chiariello, et al, ), arranged in a hierarchy of domains‐within‐domains, extending across chromosomal scales up to comprise entire chromosomes. Chromatin also forms hubs of interchromosomal interactions as those found around the nucleolus and nuclear speckles (Quinodoz et al, , and references therein), along with hundreds of large, gene‐repressive domains associated with the nuclear lamina (LADs) that also contribute to the organization of the genome inside the nucleus (van Steensel & Belmon, ). Importantly, it has been shown that diseases, such as congenital disorders and cancer, can be linked to chromatin misfolding (Lupiáñez, Kraft, Heinrich, et al, ; Valton & Dekker, ; Weischenfeldt et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…In higher eukaryotes, the genome is organized into hierarchical folding of chromosomes in highly ordered three-dimensional structures. As revealed by chromosome conformation capture (3C) assays, chromosomes are divided into territories of A (active) and B (inactive) compartments [ 82 , 83 , 84 , 85 ], which are further partitioned into topologically associating domains (TADs). Within each TAD territory, gene interactions are enriched and largely stabilized by the architectural proteins, such as CTCF [ 86 , 87 , 88 ] and cohesion [ 89 , 90 ].…”
Section: Identification Of Pioneer Factors—biochemical and Genome-mentioning
confidence: 99%